The Role of Geotechnical Monitoring at Design of Foundation Structures and their Verification – Part 1 - Drusa Marián; Vlček Jozef; Orininová Lucia (Civil and Environmental Engineering, 2016)
For a long time, design of the square foundations has not posed a problem in engineering practice. Foundations are designed on the basis of determining the bearing capacity of the subsoil, where irregularities in its determination oftentimes affect the efficiency (economy), while possible failures of bearing resistance of foundation soil are rare. More important factor is the resulting deformation of second limit state under consideration - settlement, relative settlement, tilting and excessive deformation. The current pressure on the cost reduction of design preparation and obtaining important data from geotechnical survey often results in many cases into adverse effects of settlement and differential settlement of foundations of the buildings. The question lies in a variety of analytical methods for assessing the service ability of limit states used in European countries as well as the underestimation of the proposal risks. Authors of the article want to document the fact that the most important influence on adequate and safe design is the most accurate determination of geotechnical parameters and the appropriate selection of the calculation method. For the purposes of explanation, Monte Carlo simulation technique was used to test a variety of geotechnical parameters, which will be presented in second part of article. If all construction processes are carried out successfully, rarely are the buildings evaluated once again. However, when the opportunity to participate in the stage of engineering survey and collection of geotechnical parameters as well as the control of the construction process by tools of geotechnical monitoring presents itself, it is valuable to perform the analysis of the entire process for pointing out hidden risks.